Hubungan Sosial Mahasiswa KKN 202 UIN-SU Medan dengan Masyarakat dalam Memajukan Pendidikan yang Berakhlakul Karimah di Desa Batu Tambun Kecamatan Padang Bolak - Muhammad Habibi Siregar; Mai Syaroh; Eka Putriani Harahap; Rahmad Hidayat Ritonga (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Social relations between KKN 202 students at UIN North Sumatra Medan (UIN-SU Medan) with the community in strengthening the relationship between KKN 202 students and the community in Batu Tambun Village, Padang Alternating District, and to promote education with good character. So with the existence of a socialization relationship, students of KKN 202 UIN-SU Medan will improve education by carrying out activities that involve the community and children in one way to improve education with good morals in Batu Tambun Village, Padang Alternating District. This study aims to find out more deeply how the social relations of KKN 202 students with the community in promoting moral education in Batu Tambun village, Padang alter district. The method used in this research is descriptive qualitative method. The data collection in this study used a field study. The study is in the form of observation and structured interviews.